Codon usage patterns and genomic variation analysis of chloroplast genomes provides new insights into the evolution of Aroideae - Xinbi Jia; Jiaqi Wei; Yuewen Chen; Chenghong Zeng; Chan Deng; Pengchen Zeng; Yufei Tang; Qinghong Zhou; Yingjin Huang; Qianglong Zhu (Scientific Reports)
Abstract Aroideae is an important subfamily of the Araceae family and contains many plants with medicinal and edible value. It is difficult to identify and classify Aroideae species accurately on the basis of morphology alone because of their polymorphic phenotypic traits. The chloroplast genome (CPG) is useful for studying on plant taxonomy and phylogeny, and the analysis of codon usage bias (CUB) in CPGs provides further insights into the intricate phylogenetic relationships among Aroideae. The results showed that the codon third position of the chloroplast genome coding sequence in Aroideae was rich in A and T, with a GC content of 37.91%. The ENC-plot and PR2-plot revealed that the codon usage bias of Aroideae was influenced by multiple factors, with natural selection as the dominant factor. Thirteen to twenty optimal codons ending in A/T were identified in 61 Aroideae species. Additionally, the comparative analysis of CPGs revealed that two single copy regions and non-coding regions were variable in Aroideae. Eight highly divergent regions (Pi > 0.064) were identified (ndhF, rpl32, ccsA, ndhE, ndhG, ndhF-rpl32, ccsA-ndhD, and ndhE-ndhG) , in which ndhE have the potential to serve as a reliable DNA marker to discriminate chloroplasts in Aroideae subfamily. Furthermore, the maximum likelihood-based phylogenetic trees constructed from complete chloroplast genomes and protein-coding sequences presented similar topologies. Principal component clustering analysis based on relative synonymous codon usage values (RSCUs) revealed that Calla was clearly deviated from Montrichardia and Anubias, and that Alocasia was closer to Colocasieae than to Arisaemateae. These findings suggest that the use of RSCU for clustering analysis could offer new theoretical support for species classification and evolution. Our research could provide a theoretical foundation for the chloroplast genetic engineering, taxonomy, and phylogenetic relationships of Aroideae chloroplasts.